2018
DOI: 10.1002/ldr.2923
|View full text |Cite
|
Sign up to set email alerts
|

The role of rapid glacier retreat and landscape transformation in controlling the post‐Little Ice Age evolution of paraglacial coasts in central Spitsbergen (Billefjorden, Svalbard)

Abstract: In Svalbard, the rapid glacier retreat observed since the end of the Little Ice Age (LIA) has transformed the geomorphology and sediment budgets of glacial forelands, river valleys, and slope systems. To date, relatively little information exists regarding the impact of such a profound glacial landscape degradation on the evolution of coastal environment. This paper addresses this deficiency by detailing the post‐LIA sediment fluxes to the coastal zone in Billefjorden, central Spitsbergen (Svalbard). We analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 91 publications
2
41
0
Order By: Relevance
“…This coastal sector, located at the southern side of Brepollen, is similar to previously observed paraglacial coastal systems in Svalbard, where coasts evolve in response to glaciofluvial sediment pulses released by land-terminating, valley-type glaciers (e.g. Zagórski et al, 2012;Bourriquen et al, 2018;Strzelecki et al, 2018). Rivers draining glacierized catchments of Signybreen, Bautbreen and Noname glacier (covering the northern slopes of Starostinfjellet) are major sediment feeders to the southern Brepollen coast.…”
Section: Signybreen Delta-merapynten Coastal Systemsupporting
confidence: 81%
See 3 more Smart Citations
“…This coastal sector, located at the southern side of Brepollen, is similar to previously observed paraglacial coastal systems in Svalbard, where coasts evolve in response to glaciofluvial sediment pulses released by land-terminating, valley-type glaciers (e.g. Zagórski et al, 2012;Bourriquen et al, 2018;Strzelecki et al, 2018). Rivers draining glacierized catchments of Signybreen, Bautbreen and Noname glacier (covering the northern slopes of Starostinfjellet) are major sediment feeders to the southern Brepollen coast.…”
Section: Signybreen Delta-merapynten Coastal Systemsupporting
confidence: 81%
“…Previous coastal studies in Svalbard have shown the strong relationship between rates of coastal progradation (mainly delta growth) and glaciofluvial activity (e.g. Bourriquen et al, 2016;Strzelecki et al, 2018). Similar observations were made along the coasts of Greenland, where rapid retreat of glaciers not only exposed new lands but also released significant amounts of sediment, leading to progradation of delta systems (Bendixen et al, 2017).…”
Section: New Paraglacial Coastal Landscapessupporting
confidence: 69%
See 2 more Smart Citations
“…In general, over the last decade, Svalbard coastal studies have been concentrated on the coastal zone response to shifts in sediment supply associated with changes in local ice masses and paraglaciation (e.g., Bourriquen et al, ; Mercier & Laffly, ; Sessford, Strzelecki, & Hormes, ; Strzelecki et al, ; Zagórski, ); ephemeric pulses of sediments from snow‐fed streams (Lønne & Nemec, ; Strzelecki, Long, & Lloyd, ); or the controls of coastal permafrost development (Kasprzak et al, ). Recent years had also brought some advances in local rocky coast systems that dominate over coastal landscape in numerous Svalbard fjords (e.g., Kasprzak et al, ; Strzelecki, ; Strzelecki, ; Strzelecki et al, ; Świrad, Migoń, & Strzelecki, ).…”
Section: Introductionmentioning
confidence: 99%